Institutional (Dis)Trust and Online Participation Roles in Vaccination Communication as Public Engagement - Rodin, Pavel (Javnost-The Public, 2023)
The study explores lay online participation in multivocal risk and crisis communication. It looks specifically at how institutional trust shapes such participation in the context of public health risks and crises. Taking the case of vaccination communication as a public engagement site, the study draws on in-depth interviews with Swedish Facebook users communicating about vaccination issues online and investigates how trust in the benevolence and competence of authorities and news media effect lay online participation. The results indicate coexisting trust and distrust when positive expectations regarding one of the dimensions (benevolence) are present alongside negative expectations regarding the other (competence). The study also demonstrates how particular trust beliefs shape online participation by identifying and describing three prominent roles deriving from these beliefs: the critics (low trust in benevolence), the ambassadors (high trust in benevolence), and the mediators (low trust in competence). Finally, the paper discusses the theoretical and practical implications of how these roles can impact multivocal risk and crisis communication in the digital environment.